2021
DOI: 10.1111/1365-2435.13913
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness modulates density‐dependent cannibalism rates in Drosophila

Abstract: Cannibalism is taxonomically widespread and can have large impacts on individual fitness and population‐level processes. As such, identifying how cannibalism rates vary in response to ecological cues is important for predicting species evolution and population dynamics. In this study, we aimed to identify several eco‐evolutionary factors that affect cannibalism rate and measure how they interacted with one another. To do this, we conducted two experiments using complimentary methods to measure how cannibalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…2). Intra‐brood competition over common resources is known to be a significant source of mortality for juveniles across a range of arthropod species, including fruit flies (Fisher et al 2021), dragonflies (Hopper et al 1996), earwigs (Dobler and Kölliker 2010), mantids (Fea et al 2014) and spiders (de Tranaltes et al 2022) to name but a few. Thus, our results may well be biologically plausible in suggesting that the extent to which MKB infections can provide relief from intra‐brood competition is an important determinant of their long‐term viability in response to temperature change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Intra‐brood competition over common resources is known to be a significant source of mortality for juveniles across a range of arthropod species, including fruit flies (Fisher et al 2021), dragonflies (Hopper et al 1996), earwigs (Dobler and Kölliker 2010), mantids (Fea et al 2014) and spiders (de Tranaltes et al 2022) to name but a few. Thus, our results may well be biologically plausible in suggesting that the extent to which MKB infections can provide relief from intra‐brood competition is an important determinant of their long‐term viability in response to temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by maternally inherited bacteria occur in at least 50% of arthropod species (Weinert et al 2015, Sanaei et al 2021). As these bacteria cannot be transmitted by males, males represent evolutionary ‘dead ends' with the potential to hinder the fitness of their female siblings via costly competitive interactions (Engelstädter and Hurst 2009, Fea et al 2014, Fisher et al 2021). Thus, many maternally inherited bacterial species have evolved to kill the male embryos of their hosts, which is expected to increase female survival, presumably via reduced intra‐brood competition (Werren et al 1986, Jaenike et al 2003, Engelstädter and Hurst 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kin discrimination also occurs in males, who can modulate male–male competition and female harm levels when they compete against related rivals (Carazo et al 2014, Le Page et al 2017). Recent evidence suggests that kin recognition in D. melanogaster might actually be critical for larvae, both in mediating cooperative feeding behaviour (Dombrovski et al 2017, Khodaei and Long 2019) and cannibalism (Fisher et al 2021). Remarkably, kin recognition in this species depends on both familiarity and relatedness, and is thought to rely mainly on cuticular hydrocarbons (Carazo et al 2014, Le Page et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One thing we do know is that for cannibalism to contribute to the regulation of animal population densities, it must be a density‐dependent process, generating increasing per‐capita mortality as densities rise. A large body of empirical evidence, including both observational and experimental studies, has demonstrated that this is generally true: per‐capita mortality rates from cannibalism rise, in many cases very strongly, with rising population density (Baskauf, 2003; Buddle et al, 2003; Elliott, 2004; Fincke, 1994; Fisher et al, 2021; Fox, 1975; Gillespie et al, 2020; Grosholz et al, 2021; Hannesson, 2018; Hopper et al, 1996; Houghton et al, 2017; Klotz & Wright, 2020; Moksnes, 2004; Oraze & Grigarick, 1989; Orr et al, 1990; Persson et al, 2003; Persson & Elliott, 2013; Polis, 1981; Strauss et al, 2016; Van Buskirk, 1989; Wagner & Wise, 1996; Wildy et al, 2001; Wissinger et al, 2010). These studies have, furthermore, demonstrated that there are multiple pathways through which cannibalism emerges as a density‐dependent process.…”
Section: Introductionmentioning
confidence: 99%